Fetal endoscopic tracheal occlusion reverses the natural history of right‐sided congenital diaphragmatic hernia: European multicenter experience. (1st March 2021) - Russo, F. M.; Cordier, A.‐G.; Basurto, D.; Salazar, L.; Litwinska, E.; Gomez, O.; Debeer, A.; Nevoux, J.; Patel, S.; Lewi, L.; Pertierra, A.; Aertsen, M.; et al.
ABSTRACT: Objective: To evaluate the neonatal outcome of fetuses with isolated right‐sided congenital diaphragmatic hernia (iRCDH) based on prenatal severity indicators and antenatal management. Methods: This was a retrospective review of prospectively collected data on consecutive cases diagnosed with iRCDH before 30 weeks' gestation in four fetal therapy centers, between January 2008 and December 2018. Data on prenatal severity assessment, antenatal management and perinatal outcome were retrieved. Univariate and multivariate logistic regression analysis were used to identify predictors of survival at discharge and early neonatal morbidity. Results: Of 265 patients assessed during the study period, we excluded 40 (15%) who underwent termination of pregnancy, two cases of unexplained fetal death, two that were lost to follow‐up, one for which antenatal assessment of lung hypoplasia was not available and six cases which were found to have major associated anomalies or syndromes after birth. Of the 214 fetuses with iRCDH included in the neonatal outcome analysis, 86 were managed expectantly during pregnancy and 128 underwent fetal endoscopic tracheal occlusion (FETO) with a balloon. In the expectant‐management group, lung size measured by ultrasound or by magnetic resonance imaging was the only independent predictor of survival (observed‐to‐expected lung‐to‐head ratio (o/e‐LHR) odds ratio (OR), 1.06 (95% CI, 1.02–1.11); P = 0.003). Until now, stratification for severe lung hypoplasia has been based on an o/e‐LHR cut‐off of 45%. In cases managed expectantly, the survival rate was 15% (4/27) in those with o/e‐LHR ≤ 45% and 61% (36/59) for o/e‐LHR > 45% ( P = 0.001). However, the best o/e‐LHR cut‐off for the prediction of survival at discharge was 50%, with a sensitivity of 78% and specificity of 72%. In the expectantly managed group, survivors with severe pulmonary hypoplasia stayed longer in the neonatal intensive care unit than did those with mildly hypoplastic lungs. In fetuses with an o/e‐LHR ≤ 45% treated with FETO, survival rate was higher than in those with similar lung size managed expectantly (49/120 (41%) vs 4/27 (15%); P = 0.014), despite higher prematurity rates (gestational age at birth: 34.4 ± 2.7 weeks vs 36.8 ± 3.0 weeks; P < 0.0001). In fetuses treated with FETO, gestational age at birth was the only predictor of survival (OR, 1.25 (95% CI, 1.04–1.50); P = 0.02). Conclusions: Antenatal measurement of lung size can predict survival in iRCDH. In fetuses with severe lung hypoplasia, FETO was associated with a significant increase in survival without an associated increase in neonatal morbidity. © 2020 International Society of Ultrasound in Obstetrics and Gynecology